Hormonal Influences on Women’s Health and Athletic Performance: Insights into the Menstrual Cycle, Menopause, Contraception, and Anabolic Steroids - Maciejczyk, Tomasz; Sadowski, Jakub; Sieńko, Antoni; Łabuś, Małgorzata; Dołęga, Julia; Mól, Piotr; Zabawa, Bartłomiej; Hudzińska , Patrycja; Papież, Łukasz Stanisław; Krzykawski , Karol (Quality in Sport, 2024)
Introduction: Hormones influence women’s health and athletic performance, managing conditions like menstrual irregularities, menopause, and osteoporosis. Therapies such as oral contraceptives and IUDs benefit millions but pose risks like breast cancer and cardiovascular events. In sports, hormonal fluctuations affect performance, with steroid abuse raising concerns. This review examines their benefits, risks, and implications. Materials and Methods: The study conducted a systematic review of the literature, utilizing databases including PubMed, NCBI, and Google Scholar. Data were obtained from clinical and experimental studies and evaluated based on methodological rigor, participant characteristics, and therapeutic outcomes. Articles lacking full-text access were excluded from the analysis. State of knowledge: Hormones profoundly influence women’s health and athletic performance, affecting the menstrual cycle, menopause, and responses to exercise. Physical activity improves cardiovascular and metabolic health but can disrupt hormonal balance with intense training. Hormonal contraceptives, anabolic steroids, and HRT impact health and performance, necessitating individualized approaches and further research. Conclusions: Hormonal balance is vital for women’s health and performance. Physical activity, contraception, and HRT have benefits but require tailored approaches to mitigate risks.